2020
DOI: 10.1128/aem.01311-20
|View full text |Cite
|
Sign up to set email alerts
|

Lysin LysMK34 ofAcinetobacter baumanniiBacteriophage PMK34 Has a Turgor Pressure-Dependent Intrinsic Antibacterial Activity and Reverts Colistin Resistance

Abstract: The prevalence of extensively and pandrug-resistant Acinetobacter baumannii leaves little or no therapeutic options for treatment for this bacterial pathogen. Bacteriophages and their lysins represent attractive alternative antibacterial strategies in this regard. We used the extensively drug-resistant A. baumannii strain MK34 to isolate the bacteriophage PMK34 (vB_AbaP_PMK34). This phage shows fast adsorption and lacks virulence genes, nonetheless its narrow host spectrum based on capsule recognition limits b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 66 publications
2
34
1
Order By: Relevance
“…In the case of native, unmodified enzymes, their combination with antibiotics seems to be much more promising. For example, the synergistic effects of endolysins and antibiotics (colistin) in vitro and in vivo therapies were shown ( Schirmeier et al, 2018 ; Abdelkader et al, 2020 ; Blasco et al, 2020 ). If developers succeed in defining an appropriate dosing schedule (beyond a single dose) as a basis for successful clinical studies for patients with confirmed infection due to drug-resistant pathogens or who experience recurrent or relapse infections, endolysins may provide an adjunctive therapy option.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of native, unmodified enzymes, their combination with antibiotics seems to be much more promising. For example, the synergistic effects of endolysins and antibiotics (colistin) in vitro and in vivo therapies were shown ( Schirmeier et al, 2018 ; Abdelkader et al, 2020 ; Blasco et al, 2020 ). If developers succeed in defining an appropriate dosing schedule (beyond a single dose) as a basis for successful clinical studies for patients with confirmed infection due to drug-resistant pathogens or who experience recurrent or relapse infections, endolysins may provide an adjunctive therapy option.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the mechanism of action of LysSS lysin, while the lysozyme-like Ablysin perforates the cell wall, followed by total cell shrinkage [ 4 , 10 ]. Abdelkader et al reported recently that LysMK34 lysin has turgor pressure-dependent antibacterial activity against A. baumannii [ 23 ]. We hypothesized that LysSAP26 would penetrate into the outer membrane and degrade peptidoglycan partly, and the damaged bacteria eventually would be lysed by force of turgor pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies report moderate antibacterial activities (<1-3 log reductions), other studies report a high bactericidal in vitro effect (>5 log reductions) [10,18,19 ]. However, assessing and comparing the potential of these lysins is complicated by the lack of standardized protocols and the variety of conditions used.…”
Section: Lysins With Intrinsic Antibacterial Activitymentioning
confidence: 99%
“…For example, dilute suspension buffers result in cells with a high intracellular turgor pressure, which are more prone to osmotic lysis by such lysins than when the turgor pressure is reduced in more physiological buffers. Also the diluent used for plating may cause osmotic effects and further affects the observed intrinsic antibacterial activity [19 ]. In addition, some studies make use of Tris as a buffer component in antibacterial assays.…”
Section: Lysins With Intrinsic Antibacterial Activitymentioning
confidence: 99%